Estrategia didáctica basada en TIC para el aprendizaje de ecuaciones de primer grado en estudiantes de octavo grado del Liceo Ciudad Capital de Bogotá. - García Fandiño, Juan Sebastián; Ramírez Correa, Jhoan Sebastián (Universidad Antonio Nariño, 2024)
This research monograph addresses the persistent challenge in the teaching and learning process of algebra in secondary education. Our objective is to apply a strategy based on communication technologies (ICT) to enhance the learning of eighth-grade students in solving first-degree equations.